2012
DOI: 10.1093/chromsci/bms165
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Indicating HPLC Method for the Determination of Darunavir Ethanolate

Abstract: A novel stability-indicating reversed-phase high-performance liquid chromatographic (HPLC) method has been developed for the quantitative determination of darunavir ethanolate, an HIV-1 protease inhibitor. The chromatographic separation was achieved using an X-Bridge C18 (150 × 4.6 mm × 3.5 µm) HPLC column in isocratic mode employing 0.01M ammonium formate (pH.3.0) buffer and acetonitrile in the ratio of 55:45 (v/v) with a flow rate of 1.0 mL/min. The detector wavelength was monitored at 265 nm and the column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The literature survey revealed that few methods have been reported for the estimation of darunavir ethanolate in bulk and dosage forms. [11] The aim of the present study was to develop and validate a new simple, sensitive, and rapid reverse-phase high-performance liquid chromatography (RP-HPLC) method for the determination of darunavir ethanolate in bulk and pharmaceutical dosage form.…”
Section: Crasmentioning
confidence: 99%
“…The literature survey revealed that few methods have been reported for the estimation of darunavir ethanolate in bulk and dosage forms. [11] The aim of the present study was to develop and validate a new simple, sensitive, and rapid reverse-phase high-performance liquid chromatography (RP-HPLC) method for the determination of darunavir ethanolate in bulk and pharmaceutical dosage form.…”
Section: Crasmentioning
confidence: 99%
“…1d). A survey of chemical literature as shown that few articles are available for the determination of fesoterodine fumarate using LC and LC-MS [47][48][49], HPLC [50][51][52], UV [53][54][55] and electrophoresis [56]. An attempt has been made to develop a simple and rapid visible spectrophotometric method for the assay of selected drugs in tablet dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…Darunavir is a protease inhibitor used in the treatment of Human Immunodeficiency Virus (HIV) infection. It is a pillar of therapy cocktail for patients with the virus [1] . Like most new drugs it presents low water solubility and poor bioavailability, leading to poor absorption in the gastrointestinal tract [2] .…”
Section: Introductionmentioning
confidence: 99%